1990
DOI: 10.1002/clc.4960130203
|View full text |Cite
|
Sign up to set email alerts
|

Myocarditis: Unresolved issues in diagnosis and treatment

Abstract: Summary: Myocarditis is an enigmatic disease. Lymphocytic myocarditis is most commonly viral in origin. Considerable evidence suggests that myocardial damage is due to an immune-mediated mechanism rather than to direct effects of the virus itself. The presentation is variable, ranging from a clinically inapparent or relatively benign illness to acute progressive heart failure and death. Although examination of the endomyocardial biopsy specimen is the "gold standard" for the diagnosis of myocarditis there are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 81 publications
1
32
0
Order By: Relevance
“…Our protocol has been previously published (8,10,12). In brief, after deparaffinization, sections were incubated with CD45 or CD68 (DAKO, Carpinteria, CA).…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Our protocol has been previously published (8,10,12). In brief, after deparaffinization, sections were incubated with CD45 or CD68 (DAKO, Carpinteria, CA).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The members of the genus Enterovirus (family Picornaviridae) are the most commonly implicated in viral myocarditis (2, 6, 8 -9). Coxsackie B virus may account for nearly 50% of cases of documented viral myocarditis (8). Many other viruses are associated with viral myocarditis, including Coxsackie A, influenza A, cytomegalovirus, and adenovirus, as well as other viruses (6,8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Key Words: cardiomyocytes Ⅲ chemokine CXCL 10 Ⅲ coxsackievirus Ⅲ myocarditis Ⅲ natural killer cells C oxsackievirus (CV)B3 has been recognized as the predominant cause of viral myocarditis in humans. 1 This disease is composed of three distinct stages including viremic injury, immune infiltration, and reclamation. 2 Earlier studies have suggested that mechanisms of viral myocarditis include direct myocyte injury by CVB3 and subsequent immune-mediated damage of the heart.…”
mentioning
confidence: 99%
“…1 This disease is composed of three distinct stages including viremic injury, immune infiltration, and reclamation. 2 Earlier studies have suggested that mechanisms of viral myocarditis include direct myocyte injury by CVB3 and subsequent immune-mediated damage of the heart.…”
mentioning
confidence: 99%